'My little beautiful mess': a longitudinal study of working-class masculinity in transition. Issue 2 (2nd April 2020) - Stahl, Garth
ABSTRACT: The study of masculinities and social change continues to gain prominence in the field of Critical Studies of Men and Masculinities (CSMM). This article presents a case study of one Anglo-Australian working-class male, Leo, as he experienced multiple transitions – from his final year at secondary school into various service sector jobs and eventually to becoming the first in his family to attend university. The article explores how he constructed his subjectivity in reference to his relationships and diverse experiences. Central to the analysis is the continual and contentious nature of identity work. Drawing on theories associated with both intersectionality and liminality (transitions, in-between-ness), the article explores Leo's journey contributing to scholarship which seeks to complicate historical conceptions of working-class masculinities. As Leo navigates different spaces, we are compelled to think about the discursive construction of masculinity in reference to social change as well as the multiple axes of inequality which inform his subjectivity.